Heterogeneous stochastic scalar conservation laws with non-homogeneous Dirichlet boundary conditions - Jiang-lun Wu (Journal of Hyperbolic Differential Equations, 2018)
We introduce a notion of stochastic entropy solutions for heterogeneous scalar conservation laws with multiplicative noise on a bounded domain with non-homogeneous boundary condition. Using the concept of measure-valued solutions and Kruzhkov's semi-entropy formulations, we show the existence and uniqueness of stochastic entropy solutions. Moreover, we establish an explicit estimate for the continuous dependence of stochastic entropy solutions on the flux function and the random source function.